Corrections to “Performance Analysis and Model Improvements for Electromagnetic Transient State Estimators” - Humberto Cunha De Oliveira; Vinicius Henrique Faria Brito; Jose Carlos De Oliveira; Isaque Nogueira Gondim (IEEE Access, 2025)
Presents corrections to the paper, (Corrections to “Performance Analysis and Model Improvements for Electromagnetic Transient State Estimators”).